The Role of Telemedicine in Improving Access to Healthcare in Remote Areas - Rajam, Diah Ayu Lestari; Syamsih, Nur; Hasryanty, Sri (Journal of Asian-african Focus in Health, 2024)
The purpose of this qualitative study is to discover how telemedicine contributed to increase access to healthcare in rural regions by looking at the point of view of both the involved healthcare professionals and of the patients. For the geographic areas that are poorly endowed with medical facilities telecommunication is seen as an efficient way of overcoming geographical barriers and shortages of medical equipment. In this study, the cross-sectional quasi-experimental design utilizes semi-structured interviews, focus group discussions and observation to establish the barriers, effectiveness, and socio-cultural factors regarding the telemedicine adoption. The study shows that telemedicine improves the possibilities of getting an initial consultation regardless of geographic distance, helps to avoid delays while finding a specialist, and creates a connection to advanced treatment. However, challenges which act as barriers include; weak internet connection, low technology literacy, and resistance to change. Inequalities and cultural shifts in patient and healthcare provider’s perceptions of technology, as well as comfort with tele-communication and tele-befriending over in-person contact, also influence the readiness of patients and healthcare officials to adopt telepharmacy. Power relations also come out in the presentation, with telemedicine holding benefits, especially for women in the inaccessible regions. The study further underscores the importance of a better appreciation of context when adopting telemedicine programs for greater improvement and sustainably. In summary, this paper adds value to extant knowledge by exploring the mediated nature of technology culture and health care delivery in hard-to-reach regions and offering direction for enhancing the use of telemedicine solutions in rural regions.